Designing and Simulation a Secure Network Using Multiple Security Technologies: Port Security, DHCP Snooping, ACL, SSH and Data Protection Type of the Paper (Applied Scientific Study) (Comprehensive Journal of Science, 2025)
The university network has also become vulnerable to potential threats due to the increase in the numbers of devices and services being connected. The following report describes the creation and simulation of a secure university network using Cisco Packet Tracer. The network incorporates the use of VLAN segregation, Port Security, DHCP Snooping, Access Control Lists, and SSH for secure management. The results demonstrate the network's connectivity, isolation, and stability for use in academic settings, as stated in [1], [2].
Keywords: University Network, Network Security, Cisco Packet Tracer, VLAN, DHCP Snooping, Access Control Lists, SSH.